PENGOLAHAN DATA GEOLISTRIK DENGAN METODE SCHLUMBERGER - Broto, Surdaryo; Sera Afifah, Rohima (TEKNIK, 2008)
Geophysics is a knowledge that concern about structural and composition in subsurface. Geophysicshas some methods to explore subsurface condition which are: seismic, gravity, geomagnetic,georesistivity, georadar and well logging. Georesistivity is one of geophysics method that focused inresistivity properties in the earth. Georesistivity has some methods which are telluric resistivity,magnetotelluric, electromagnetic, IP (Induced polarization), resistivity. Resistivity can be divided intoHorizontal Profilling (HP) and Vertical Electrical Sounding (VES). Georesistivity is used for shallowinvestigation effectively.